Policies and regulatory instruments. An environmental strategies focused on management based in participation - Guzmán Luján, Hector Enrique (Corporación Universitaria del Caribe, CECAR., 2014)
Day after day the public opinion contemplates how Colombia, diverse country and gifted of great wealth in biodiversity, is diminishing qualitatively and quantitatively his resources, affecting not only the quality of life in our principal cities, but the possibility of using this wealth rationally as engine of development. This article raises as aim, a reflection on the need and relevancy of restating the environmental strategies used at present and asks, if really these prevent the gradual deterioration of the natural resources, and if really they guarantee the constitutional law of the article 79, named right to enjoy a healthy environment. To methodological level, this work arises from a documentary review, and raises as discussion the reflection on environmental strategies in the national and international area to confront the environmental problematics in the productive sector. As conclusion emphasizes that in Colombia, in spite of possessing multiple coercive instruments in environmental matter, these are not constituted in a solution of bottom to the problematic ones that they attack, a politics is necessary in the matter, which could create tools of market, agreements of automanagement and this way strengthen the relations between the public and private thing. ___Resumen: Día a día la opinión pública contempla cómo Colombia, país mega diverso y dotado de gran riqueza en biodiversidad, va disminuyendo cualitativa y cuantitativamente sus recursos, afectando no solamente la calidad de vida en nuestras principales ciudades, sino la posibilidad de utilizar esa riqueza racionalmente como motor de desarrollo. Este artículo plantea como objetivo, una reflexión sobre la necesidad y pertinencia de replantear las estrategias ambientales utilizadas en la actualidad, y pregunta si realmente éstas impiden el paulatino deterioro de los recursos naturales, y si efectivamente garantizan el derecho constitucional del artículo 79, denominado derecho a gozar de un medio ambiente sano. A nivel metodológico, este trabajo surge de una revisión documental, y plantea como discusión la reflexión sobre estrategias ambientales en el ámbito nacional e internacional para afrontar la problemática ambiental en el sector productivo. Como conclusión destaca que en Colombia, a pesar de contar con múltiples instrumentos coercitivos en materia ambiental, éstas no se constituyen en una solución de fondo a las problemáticas que atacan, es necesaria una política en la materia, que pueda crear herramientas de mercado, acuerdos de autogestión y así fortalecer las relaciones entre lo público y privado. ___Palabras clave: Estrategias Ambientales, Biodiversidad, Producción y Consumo Sostenible. ___Recibido febrero 28 de 2014 / Aceptado abril 29 de 2014